Assessment of torque ripple minimization techniques for aircraft switched reluctance machine starter/generator - Ding, Xiaofeng; Rashed, Mohamed; Bozhko, Serhiy (2017)
This paper presents an assessment of different torque ripple minimization techniques for more electric aircraft Switched Reluctance Machine (SRM) starter/generator (S/G). SRM is one of the most popular potential candidates for future aircraft S/G. SRM is a type of electric machine that features simple structure hence it is cheap to manufacture, also it is very robust. However, one of the major disadvantages of SRM is that, due to its structural nature, its highly nonlinear characteristics would result in unwanted torque ripple. In order to eliminate/minimise the torque ripple, some techniques were proposed over the last decades. In this paper, several techniques of Torque ripples minimization (TRM) are introduced and then it focuses on the assessment of two techniques suitable for the proposed 45 kW SRM as S/G, namely torque sharing function (TSF) technique and a newly proposed closed-loop torque control (CLTC) technique. An analytical modelling method is also proposed in order to apply the proposed TRM techniques. Conclusions and future works are presented at the end of this paper.